UTILISATION OF SLAG POWDER FOR CEMENT SUBSTITUTION BASED ON THE COMPRESSIVE STRENGTH AND PENETRATION OF CHLORIDE IONS - Yasmina Amalia; Syoni Soepriyanto (Jurnal Sains Materi Indonesia, 2019)
UTILIZATION OF SLAG POWDER FOR CEMENT SUBSTITUTION BASED ON THE COMPRESSIVE STRENGTH AND PENETRATION OF CHLORIDE IONS. The availability of waste from nickel ore smelting in the form of slag has increased, this is due to the high nickel production to meet the increasing needs for development and for compound- ing materials for construction materials. This research aims to make a paste from the mixture of Nickel Pig Iron (NPI) slag from PT Indoferro which is used as a substitute for making cement paste. The materials used in this study are cement, nickel slag, water, and zeolite. The cement paste is made with a dimension of 10 cm x 5 cm with each slag used as an amplifier on the paste with a volume variation of 15%, 30%, 45%, and 60%. Each material is weighed according to mix design then mixing the materials, after they are homogeneous, they are put into the mold and then let stand for 24 hours until the paste solidifies and hardens, after 24 hours, the paste sample is removed from the mold and treated at room temperature, after the life is qualified, the paste sample is tested. Results of the compression test show that variations of slag addition to the paste mixture giving maximum compressive strength is the 15% variant for NPI slag. The increase in compressive strength of the slag mixture paste may occur because slag contains cement compounds which can chemically react with Calcium Hydroxide (CH) com- pounds as a result of the hydration reaction of cement with water to form a Calcium Silicate Hydrate (CSH) compound from the hydration result between water and cement to increase adhesion and compressive strength on cement paste.